STIMULASI TUNAS PISANG BARANGAN (Musa acuminata L.) SECARA IN VITRO DENGAN BERBAGAI KONSENTRASI IBA (Indole-3-butyric acid) DAN BA (Benzyladenin) - Sihotang, Saipul (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2016)
The research aim was get the best medium combination of IBA dan BA to stimulated formation number of shoots of banana Barangan. The study used factorial experiment aranged in Completely Randomized Desigh (CRD). The treatment consisted of 2 factors. The frist factor was the IBA concentration, consisted of three levels 0,0 mg/l, 0,5 mg/l, and 1,0 mg/l. The second factor was BA concentration consisted of four level, 0,0 mg/l, 1,5 mg/l, 3,0 mg/l, and 4,5 mg/l. The result showed that combinations of IBA 0,0 mg/l and BA 0,5 mg/l was the best medium to induce shoot multiplication with 4,00 shoots explant. IBA concentrations had no significant effect on number of shoots. However, the IBA concentation affected the number of root explant.